Comparative study on indoor fungi growth incorporated with different antifungal and wall finishings - Subramaniam, Menega (2017)
Indoor air quality is important to the health and comfort of building occupants. There are many sources of pollutants that can be found in the building. One of the sources of pollutants is fungus. Fungi are present almost everywhere in indoor and outdoor environments. Building materials supporting fungal growth must be remediated as rapidly as possible in order to ensure a healthy environment. The goal of this study is to compare the growth of indoor fungal by using three different antifungals such as potassium sorbate, zinc salicylate and calcium benzoate. The indoor fungi were isolated from selected room at Faculty of Civil and Environmental Engineering (FKAAS). The objective is to enumerate the growth of indoor fungal after incorporate with antifungal at different types of wall finishes and evaluate its efficiency. This research was done on three main substrates which are wood, plasterboard and concrete. These main materials were each coated with four types of coating which are thin wallpaper, thick wallpaper, glycerol based paint and acrylic paint. The growth rate was monitored as all the materials was applied with the antifungal. The antifungal has reduced the growth rate of the fungus but depending on the type of material and coating that is used. Results shows that for wood substrate, the best antifungal treatment is a mix of thick wallpaper and calcium benzoate, where the growth stops at 53% (CB 53% < PS 87% < ZS 90% < CTRL 93%). As for plasterboard substrate, thin wallpaper and potassium sorbate hinders the growth at 40% (PS 40% < ZS 73% < CB 80% < CTRL 97%) whereas for concrete substrate, acrylic paint and glycerol based paint incorporated with calcium benzoate renders the growth of fungi to stop at 0% throughout the test (Acrylic Paint = CB 0% < ZS 7% < PS 7% < CTRL 33%) and (Glycerol Based Paint = CB 0% < PS 70% < ZS 73% < CTRL 87%). Thus, the best building material would be concrete with the application of calcium benzoate for paint type of wall finishing’s.